Practice to Theory: Making Connections Between Assessment and Evaluation Through a Reflective Practice Assignment in the Bachelor of Education Program - Terri Jackson (Canadian Journal for the Scholarship of Teaching and Learning)
In self-study, researchers explicitly identify how their practices add to the body of knowledge in teacher education (Vanassche & Kelchtemans, 2015). This self-study aims to document and analyze some of my learning as an early career teacher educator in Ontario, Canada. Being cognizant of the well-researched theory-to-practice gap in teacher education and the potential for someone with recent field experience to readily share “tips and tricks” without deeply connecting to theoretical perspectives (Hibbert et al., 2022), I document and analyze my experiences shifting the structure of a Bachelor of Education course assignment. The purpose of the shift is to help support teacher candidates in drawing connections between their assessment practices on placement and assessment theory and policy. Through this reflective essay, I share my instructional decisions, how I enacted them, and reflect forward. Because teacher candidates demonstrated clear connections about how their assessment decisions aligned with theory, policy, and curriculum documents, I believe this assignment was a successful addition to the course.